2024
DOI: 10.1186/s41016-024-00360-9
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of the EMBOPIPE flow diverter device: in vivo and in vitro experiments

Yongnan Zhu,
Fanyan Zeng,
Jian Liu
et al.

Abstract: Background Although flow diverter device (FDD) has brought revolutionized advances in endovascular treatment of intracranial aneurysms, it also presents considerable drawbacks as well, as the innovation for novel device has never stopped. This preclinical research aims to evaluate the safety and efficacy of a newly developed FDD, the EMBOPIPE, through in vivo and in vitro experiments. Methods Aneurysms were induced in 20 New Zealand white rabbits w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Following publication of the original article [ 1 ], the authors reported that the authorship needed to be updated. They want to change the author Xinjian Yang to the main corresponding author and the author Ying Zhang to the co-corresponding author, interchanging the order of the authors Yangxin Jian and Ying Zhang.…”
mentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors reported that the authorship needed to be updated. They want to change the author Xinjian Yang to the main corresponding author and the author Ying Zhang to the co-corresponding author, interchanging the order of the authors Yangxin Jian and Ying Zhang.…”
mentioning
confidence: 99%